Association of CHA2DS2-VASc-HS Score with Adverse In-hospital Outcomes in Patients with Non-ST Segment Elevation Myocardial Infarction (Cardiovascular Journal, 2019)
Background: Early detection of patients with non-ST segment elevation myocardial infarction (NSTEMI) who would suffer from adverse in-hospital outcomes is important for the therapeutic decision. Recently it was described that CHA2DS2-VASc-HS and CHA2DS2-VASc score is a predictor for severity and adverse in-hospital outcomes in patients with stable coronary artery disease (CAD) and acute coronary syndrome. The aim of our study was to assess the accuracy of the CHA2DS2-VASc-HS score predicting adverse inhospital outcomes in NSTEMI patients.Methods: 120 patients with NSTEMI were enrolled in this study. The CHA2DS2-VASc-HS score was calculated. The study subjects were divided into two groups. Patients’ with CHA2DS2-VASc-HS score>4 were put into group I and scored” 4 into group II. They were treated as per hospital treatment protocol and followed-up for adverse in-hospital outcomes (Heart failure, cardiogenic shock, recurrent ischemic pain, significant arrhythmia and death).Results: It was observed that, patients with CHA2DS2-VASc-HS score >4 had more adverse in-hospital outcomes than CHA2DS2-VASc-HS score d” 4 (20% vs. 3.3%, p=0.01). Group I patients developed cardiogenic shock 10%, heart failure 4%, recurrent ischemia 11.7%, significant arrhythmia 1.7% and death 1.7% than group II patients (1.7%, 3.3%, 3.3%, 0% and 0% respectively). By risk measurement, CHA2DS2-VASc-HS score >4 emerged as a risk factor for developing adverse in-hospital outcome (Relative risk=6).Conclusion: NSTEMI patients with high CHA2DS2-VASc-HS score have more adverse in-hospital outcomes. This score, which involves only clinical parameters, can be used as a predictor of outcomes in this group of patients.Cardiovasc. j. 2019; 11(2): 159-166